Sub-exact sequence of rough groups - Setyaningsih, Nevi; Fitriani, Fitriani; Faisol, Ahmad (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
Rough Set Theory (RST) is an essential mathematical tool to deal with imprecise, inconsistent, incomplete information and knowledge Rough Some algebra structures, such as groups, rings, and modules, have been presented on rough set theory. The sub-exact sequence is a generalization of the exact sequence. In this paper, we introduce the notion of a sub-exact sequence of groups. Furthermore, we give some properties of the rough group and rough sub-exact sequence of groups.